Downshifting as the Search for the Concept «Affinity» in the Social and Cultural Life of Modern Ukraine - M. V. Aleksandrova (Культура України, 2018)
Relevance. The relevance of the research is caused by the transformation process taking place in the social and cultural life of modern Ukraine. The aim of the paper is to analyze the cultural codes of the rural society being cultivated in the cultural life of the medieval Ukraine and later, being transformed into the downshifting lifestyle practice as well as the potentials of the downshifting as the social phenomenon where the new type of the «post-villager» is likely to appear in the cultural life of Ukraine. Research methodology. Colturological approach is the basic one. Besides, the axiological approach, the descriptive method, the comparative analysis method and the generalization method are being used. Results. The peculiarity of the Ukrainian downshifting is based on the fact, that the representatives of the creative group of society do not advertize the lifestyle change which is absolutely harmonious and logical. Being based on the cultural codes of the rural society, it is, preferably, the lifestyle norm for the Ukrainian citizens than protesting or excaping. The explication of the mentioned cultural codes is crucial when studying modern and past trauma events. The trauma loses in the Ukrainian histori include the violation of the traditional rural lifestyle on the basis of the civil society. It is a fact, that the modern Ukrainian civil groups become relevantly active afer the abolishment of the rural civil groups in the period of collectivization. The analyzed data, can potentially bring to different types of downshifting in Ukrainе, the cultivation of the group of sociaty who is looking for the «affinity» and the so-called «simple living», being based on tht agrarian means of production and the «rural phylosophy». Novelty is triggered by the research aspect choiсe. The peculiarities of the Ukrainian downshifting has not been the subject of the culturological analysis. The practical significance. The research data help to give the details of the peculiarities of the development of the Ukrainian society. They can be used when lecturing the compulsary and elective courses in the «History of Ukrainian Сulture». Key words: downshifting, lifestyle practice, cultural codes, urban, rural.